2013
DOI: 10.1681/asn.2013010049
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Race and Income on Living Kidney Donation in the United States

Abstract: Studies of racial disparities in access to living donor kidney transplantation focus mainly on patient factors, whereas donor factors remain largely unexamined. Here, data from the US Census Bureau were combined with data on all African-American and white living kidney donors in the United States who were registered in the United Network for Organ Sharing (UNOS) between 1998 and 2010 (N=57,896) to examine the associations between living kidney donation (LKD) and donor median household income and race. The rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
69
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(75 citation statements)
references
References 32 publications
4
69
0
Order By: Relevance
“…Since 2006, national living kidney donation rates have declined, a decrease some have ascribed in part to the downturn in the economic climate in the United States (1,12). Relatively compelling evidence indicates that socioeconomic status is an important factor in access to kidney transplantation (5,14,15). Because transplant candidates are likely to seek donors from similar socioeconomic backgrounds, the lower rate of LDKT among patients with lower socioeconomic status may in part be due to the perceived or actual financial effect that donation may have on potential donors.…”
Section: Background On Systemic Barriers To Living Kidney Donationmentioning
confidence: 99%
“…Since 2006, national living kidney donation rates have declined, a decrease some have ascribed in part to the downturn in the economic climate in the United States (1,12). Relatively compelling evidence indicates that socioeconomic status is an important factor in access to kidney transplantation (5,14,15). Because transplant candidates are likely to seek donors from similar socioeconomic backgrounds, the lower rate of LDKT among patients with lower socioeconomic status may in part be due to the perceived or actual financial effect that donation may have on potential donors.…”
Section: Background On Systemic Barriers To Living Kidney Donationmentioning
confidence: 99%
“…Precisely how many potential donors choose not to donate because of anticipated financial hardship is currently unknown and warrants investigation, but it is not unreasonable to suggest that these concerns may have contributed to the recent LKD decline during the economic recession in the United States. Indeed, Gill et al (47,48) found that LKD increased the most among those in higher-income groups from 1999 to 2004; however, since 2004, LKD has declined the most in low-income groups, thus accelerating the income difference in LKD rates. In addition, the LKD decline has been most dramatic in low-income blacks relative to all other racial/ethnic and income groups (47).…”
Section: Incomementioning
confidence: 99%
“…Indeed, Gill et al (47,48) found that LKD increased the most among those in higher-income groups from 1999 to 2004; however, since 2004, LKD has declined the most in low-income groups, thus accelerating the income difference in LKD rates. In addition, the LKD decline has been most dramatic in low-income blacks relative to all other racial/ethnic and income groups (47).…”
Section: Incomementioning
confidence: 99%
See 1 more Smart Citation
“…1,10 Patients undergoing home dialysis are healthier, have better social support and socioeconomic status, and assume greater responsibility for their own care. 3,11,12 It is, thus, reasonable to postulate that racial/ethnic disparities in transplantation rates may not exist among individuals undergoing PD or home HD.…”
mentioning
confidence: 99%